Double‐Coated Fe2N@TiO2@C Yolk‐Shell Submicrocubes as an Advanced Anode for Potassium‐Ion Batteries†. Issue 7 (27th May 2021) - Du, Yichen; Weng, Wangsuo; Zhang, Zhuangzhuang; He, Yanan; Xu, Jingyi; Yang, Tian; Bao, Jianchun; Zhou, Xiaosi
Main observation and conclusion: Rationally designing inexpensive iron nitrides that have large conductivity, high theoretical capacity, and rapid ionic diffusion kinetics is of great importance for realizing their practical application in potassium‐ion batteries. In this work, we have constructed double‐shelled Fe2 N@TiO2 @C yolk‐shell submicrocubes with porous Fe2 N yolk as an anode material for stable and high‐rate capability potassium‐ion batteries. This special structure can effectively buffer the large volume variation of electrode during cycling, supply abundant reaction sites to host potassium ions, and enhance electronic conductivity of the electrode material. Benefiting from these structural and compositional advantages, the Fe2 N@TiO2 @C yolk‐shell submicrocube anode delivers high specific capacity, long‐term cyclability, and remarkable rate property. Abstract : Double‐shelled Fe2 N@TiO2 @C submicrocubes with porous Fe2 N yolk are successfully fabricated by a multistep templating method. Benefiting from the structural and compositional merits, the as‐obtained Fe2 N@TiO2 @C yolk‐shell submicrocubes deliver high specific capacity, long‐term cyclability, and remarkable rate property.